Peran Hukum Agraria dalam Pengelolaan Tanah Pesisir Studi Kasus Pagar Laut di Tangerang - Surur Roiqoh; Navirta Ayu (CV Putra Publisher, 2025)
Coastal land management in Indonesia, particularly in Tangerang, faces significant problems related to the unclear legal status of land and conflicts of ownership between local communities, businessmen, and the government. Land that has been controlled by the community for generations without a valid certificate is often a source of dispute, and development projects such as sea fences exacerbate tensions between various interests. Indonesia's agrarian law, as regulated in the Basic Agrarian Law No. 5 of 1960 (UUPA), has a crucial role in regulating coastal land rights, dispute resolution, and land rights mapping. Regional autonomy gives local governments the authority to manage coastal land by taking into account the interests of local communities and environmental sustainability. However, the main challenges faced are limited resources, poor coordination between central and local governments, and the protection of indigenous peoples' rights. Therefore, strengthening the capacity of local governments, formulating clear spatial policies, and improving coordination between relevant parties are essential to ensure fair and sustainable coastal land management. This study aims to provide insights into coastal land management in Indonesia and solutions to overcome obstacles in the implementation of agrarian policies and regional autonomy.